2024
DOI: 10.1007/s11010-024-04926-0
|View full text |Cite|
|
Sign up to set email alerts
|

TRPM2 knockdown attenuates myocardial apoptosis and promotes autophagy in HFD/STZ-induced diabetic mice via regulating the MEK/ERK and mTORC1 signaling pathway

Feng Hu,
Chaoyang Lin

Abstract: Diabetic cardiomyopathy (DCM) is a major complication of diabetes. Transient receptor potential melastatin 2 (TRPM2) activity increases in diabetic oxidative stress state, and it is involved in myocardial damage and repair. We explore the protective effect of TRPM2 knockdown on the progression of DCM. A type 2 diabetes animal model was established in C57BL/6N mice by long-term high-fat diet (HFD) feeding combined with a single injection of 100-mg/kg streptozotocin (STZ). Genetic knockdown of TRPM2 in heart was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…As already reported before in this paragraph, diabetes is often associated with cardiomyopathy; in this regard, it has been suggested that in a pharmacological model of diabetes obtained by treating the animals with streptozotocin, mice show an enhancement of myocardial apoptosis associated with an inhibition of autophagy in the heart. Such effect is completely reversed by the knockdown of the transient receptor potential melastatin 2 gene which modulates autophagy processes ( Hu and Lin, 2024 ). Also, the kidney is an organ that might undergo pathological changes during a condition of hyperglycemia, and a very complex and recent study evidenced that inflammation, the increase of oxidative stress, and altered autophagy contribute to the development of diabetic kidney disease ( Jianbing et al, 2022 ).…”
Section: Diabetesmentioning
confidence: 99%
“…As already reported before in this paragraph, diabetes is often associated with cardiomyopathy; in this regard, it has been suggested that in a pharmacological model of diabetes obtained by treating the animals with streptozotocin, mice show an enhancement of myocardial apoptosis associated with an inhibition of autophagy in the heart. Such effect is completely reversed by the knockdown of the transient receptor potential melastatin 2 gene which modulates autophagy processes ( Hu and Lin, 2024 ). Also, the kidney is an organ that might undergo pathological changes during a condition of hyperglycemia, and a very complex and recent study evidenced that inflammation, the increase of oxidative stress, and altered autophagy contribute to the development of diabetic kidney disease ( Jianbing et al, 2022 ).…”
Section: Diabetesmentioning
confidence: 99%